Condiments, their classification, adulteration, and dietetic effect - Davis, Edith Nellie (My University, 1905)
Introduction: The word "condiment" is usually defined in etymological works as that which is used along with something else to preserve or pickle. It comes from the Latin noun condimentum which is derived from the Latin verb condio meaning I preserve or pickle. No doubt the word condiment originally included only aromatic substances capable of preserving or helping to preserve food from spoiling, but its meaning has extended and we now include under the title "condiments" all the saline, mineral, acid, and sweet vegetable substances, spices and aromatic materials and herbs. It may be helpful further in understanding the substances included and their relation to give a classification of the more common and universally used. Condiment Thudichum arrange them in groups about as follows:- GROUP.I. Saline Condiments. 1. Common salt (Sodium Chloride). 2. Saltpetre or Nitre (Nitrate of Potash). This latter is used with common salt for preserving meat. Its particular function seems to be to maintain and heighten the color of the flesh. GROUP. II. Peppery Substances. 1. Black and White Pepper. .Black pepper is the ground berry of the plant Piper Nigrum.
Citation: Davis, Edith Nellie. Condiments, their classification, adulteration, and dietetic effect. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Aromatic Substances; Parts of Cruciferous and Composite Plants with Sharp Oil; Theses